Konseling untuk Mengatasi Problematika dalam Kehidupan Pernikahan (Studi Fenomenologi terhadap Keluarga Sakinah di Kalimantan Barat) - Hidayati, Sri; Kartadinata, Sunaryo; Ahman, Ahman; Sugandhi, Nani (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This research departs from concerns over the increasing divorce rate in Indonesia from year to year, which requires attention from various parties, including the counselor profession. This study aims to describe the problems husbands and wives face in married life and their experiences in solving these problems. The researchers formulated the marriage counseling process and stages based on the existing problems to help couples find problem-solving. This study uses a qualitative method with a phenomenological approach to reveal the experiences of married couples related to problems and how they solve the problem. The unit of analysis of this study consisted of 14 couples who won the Sakinah Teladan Family in West Kalimantan Province. Data analysis uses phenomenological analysis procedures and is assisted by Nvivo 12 Pro software. The research findings are: (1) problems faced by participants who have been married for more than 30 years include differences of opinion, partner behavior, jealousy, family problems, communication, and financial difficulties, (2) how participants solve the problems they face, namely: the existence of mutuality, being silent, deliberation, not involving parents, arguing, adhering to a religion, introspection, understanding the character of a partner, solving problems immediately, parents being role models for children, and developing a humorous attitude, and (3) a series of processes and the stages of counseling to help overcome the problems of married couples can be carried out in four phases, including the pre-session planning and task stage, the initial session or the initial stage, the mid-counseling phase, and the termination stage.